The Genetic Diversity of TLR4 MHC-DRB Genes in Dairy Goats Using PCR-RFLP Technique - M Petlane; R R Noor; R R.A Maheswari (Faculty of Animal Science, Bogor Agricultural University, 2012)
This research was aimed at evaluating the genetic polymorphism of TLR4 and MHC-DRB genes in dairy goats [(Saanen, Etawah Grade-Saanen Crossbred (PESA), and Etawah Grade (PE)] using PCR -RFLP. The two genes are involved in immunity where they play a crucial role in pathogens recognition and presentation to T-cells and CD4 cells. PCR was used to amplify genomic DNA for TLR4 (382 bp) and CaLA-DRB (285 bp) genes fragments. Genetic polymorphism was detected by digesting TLR4 amplimer with AluI while DRB amplimers were digested with PstI and TaqI in two separate reactions. The results showed that TLR4|AluI was monomorphic and fixed with allele T in all three breeds while DRB|TaqI and DRB|PstI loci were found polymorphic for all breeds. Heterozygosity expected (He) and PIC were found low at both DRB|TaqI and DRB|PstI loci in PE and Saanen. Χ2 results showed that DRB|PstI in PE and DRB|TaqI in PESA were not in H-W equilibrium and did not display homozygous recessive genotype. The results declared that TLR4|AluI was not a good for marker for diseases resistance whereas DRB|TaqI and DRB|PstI gave hope for resistance based on their PIC.